Taguchi experimental design for electrocoagulation process using alternating and direct current on fluoride removal from water. Issue 27 (8th June 2016) - Ghanizadeh, Ghader; Shariati neghab, Gholamreza; Salem, Mohammad; Khalagi, Kazem
Abstract: Taguchi experimental design with the alternating and direct current (AC and DC) electrocoagulation (EC) using initial fluoride concentration of contaminant, retention time, pH, electrode type, and voltage was used on fluoride removal. DC current is significantly more efficient than AC, and Al has a higher performance than Fe electrode ( p  < 0.05). Neutral pH is more effective than acidic and alkaline condition in which significant differences are observed in reaction time of 60 min ( p  = 0.02). Elevation of cell potential from 15 to 25 V led to enhancing efficiency, but beyond these range fluoride removal declined. Fluoride concentration increase from 3 to 8 mg/l declined the EC performance with a significant impact in reaction times of 20 and 40 min ( p  = 0.004). In similar cell potential, increasing in reaction time from 20 to 60 min led to decreasing in residual fluoride from 1.75 to 1.06 mg/l, and 1.64 to 0.76 mg/l in 25 and 40 V, respectively.